POLICY IMPLEMENTATION OF A HEALTHY INDONESIA PROGRAM WITH A FAMILY APPROACH IN BANDUNG DISTRICT - Zaenuri, Uri; Arifianti, Ria; Dai, Ratna Meisya (Advances in Social Sciences Research Journal, 2021)
The purpose of this study was to determine the implementation of the Healthy Indonesia Program with a Family Approach which is indispensable as a determinant of the success of the Bandung Regency Government’s performance in the health sector. The Healthy Indonesia Program with a Family Approach is a priority program of the Ministry of Health which is implemented by the Center for Community Health. The implementation of the Healthy Indonesia Program with a Family Approach in Bandung Regency was only carried out in 2017 with program socialization activities at the Health Office and Community Health Center levels. The research method used is descriptive qualitative with the approach of Donald van Meter and Carl van Horn’s policy implementation model. The findings from the implementation of the Healthy Indonesia Program with a Family Approach in Bandung Regency have been implemented but have not yet reached the target of total coverage. The Bandung Regency Healthy Family Index is included in the unhealthy assessment (<0.8). So that the success of implementation will be achieved when making improvements from deficiencies, both in terms of standards and policy targets or policy measures and objectives, resources, characteristics of the implementing organization, attitudes of the implementers, communication between organizations and implementing activities, and the social, economic and political environment. Suggestions from this study are to improve the empowerment of family roles and community potential with training methods for community cadres, continue the enumerator recruitment program to assist with home visits and data collection and data input, advocate for budget allocations sourced from regional revenue and expenditure budgets.